THE PERFORMANCE TEST OF DIESEL ENGINE WITH A COMBINATION OF BIODIESEL AND PYROLYSIS OIL - Gunawan Budi Susilo; Beni Tri Sasongko (Jurnal Dinamika Vokasional Teknik Mesin, 2023)
The need for fuels is increasing and almost entirely derived from fossil fuels. The one of technology to reduce fossil fuel consumption is the pyrolysis method. Pyrolysis is defined as a chemical degradation reaction caused by heat in the absence of oxygen. Pyrolysis of plastic waste into liquid fuels, using a batch reactor, is set at a temperature of 450oC. This study was conducted to determine plastic waste pyrolytic oil properties of LDPE50 %+ Other50 % blend, such as specific gravity, kinematic viscosity, pour point, water content, and ash content. The results of mass balance calculations produce 43,41 %wt liquid, 5,0 %wt solid, and 51,59 %wt gas. The results showed that the value of specific gravity was 0.881, kinematic viscosity 1.162 mm2s, pour point of -12oC, water content 0.8 %vol, and ash content 0.062 %wt.  Diesel engine performance which uses a mixture of fuel from a result of pyrolysis process of (5 %vol and 10%vol) and biodiesel (90 %vol and 80 %vol) are tested to the Engine Test Bed Nissan Diesel SD22 Series. The results showed that the maximum torque at 1800 rpm is 122.919 Nm, which has the same value as mixed plastic waste pyrolytic oil 10 %vol to 100 % biodiesel. Maximum power at 2500 rpm is 30.3259 kW, which has the same value as mixed plastic waste pyrolytic oil 10 %vol to 100 % biodiesel.